Effect of Buprenorphine on Characteristics of Ultrasound-Guided Supraclavicular Brachial Plexus Block With Levobupivacaine and Bupivacaine-A Prospective Double-Blind Randomized Controlled Trial - Pushpavathi Ture; Ashwini H R; Jyothi B; Ajay Ture; Likhith L M; Kalaivani S (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Background The use of ultrasound in supraclavicular brachial plexus block has improved the success rate of block with excellent localization and improved safety margin. Reports of toxicity with levobupivacaine are scarce, yet it has not entirely replaced bupivacaine in clinical practice. Aims/Objectives We investigated the anesthetic potency with onset of sensory block as primary objective between bupivacaine with buprenorphine and levobupivacaine with buprenorphine for supraclavicular block in patients undergoing upper limb surgeries. Methods This randomized prospective double-blind study was conducted on sixty patients 18 to 60 years of age. Twenty ml of either inj bupivacaine 0.5% (Group A) or inj levobupivacaine 0.5% (Group B) with 2mcg/kg of inj buprenorphine was injected using a portable ultrasound machine with a linear ultrasound transducer (8–13 MHz). Distension of the brachial plexus sheath was considered as an indication of correct needle placement. The time of onset and duration of sensory and motor block were noted. RESULTS Mean onset of sensory block was comparable between the two groups. However, mean onset of motor block was faster in group A compared to group B which was statistically significant. Conclusion The anaesthetic efficacy of levobupivacaine in supraclavicular brachial plexus block was similar to bupivacaine in the onset of sensory block, however onset of motor block was faster with racemic bupivacaine